Autobiograficzna refleksja Prudencjusza nad własnym życiem u progu starości - Kołosowski, Tadeusz (Vox Patrum, 2011)
The author analyses the beginning of the poetic work of Prudentius (Praefatio) in whom the poet does the self-examination over his own previous life. The poet runs short his own past: the childhood, the beginning of rhetorical studies , errors of the youth, the lawyer’s career , finally the development of the public career. This are quick scenes from following stages of his life. The poet considers, how to live the period of the old age. One ought to talk with himself, to perform the dialogue with the own soul. The old age is the time which man should think about God. The poet wants to laud God with his own word, with her own poetry. Prudentius expresses the conviction that his poesy, lauds God with the day and by night, praises apostles and martyrs, fights with the idolatry and heresies and explains Catholic faith. Such poetry will assure him the salvation.